Enhanced LWIR response of InP/InAsP quantum discs-in-nanowire array photodetectors by photogating and ultra-thin ITO contacts - Jeddi, Hossein; Adham, Kristi; Zhao, Yue; Witzigmann, Bernd; Römer, Friedhard; Bermeo, Marie; Borgström, Magnus T.; Pettersson, Håkan (Nanotechnology, 2024)
Here we report on an experimental and theoretical investigation of the long-wavelength infrared (LWIR) photoresponse of photodetectors based on arrays of three million InP nanowires with axially embedded InAsP quantum discs. An ultra-thin top indium tin oxide contact combined with a novel photogating mechanism facilitates an improved LWIR normal incidence sensitivity in contrast to traditional planar quantum well photodetectors. The electronic structure of the quantum discs, including strain and defect-induced photogating effects, and optical transition matrix elements were calculated by an 8-band k·p simulation along with solving drift-diffusion equations to unravel the physics behind the generation of narrow linewidth intersubband signals observed from the quantum discs.
CRIS-Team Scopus Importer:2024-07-19
Keywords: infrared photodetectors; long-wavelength infrared (LWIR); nanowire array photodetectors; nanowires; photogating; quantum discs-in-nanowires; ultra-thin ITO contacts